2010
DOI: 10.1007/s00374-010-0472-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conventional and minimum tillage on physical and biochemical stabilization of soil organic matter

Abstract: The objectives were to investigate (1) to which extent water-stable macro-and microaggregates sequester organic matter (OM) in a minimum tillage (MT) system compared to a conventional tillage (CT) system and (2) if the content of biochemically stabilized OM differs between both tillage systems, and (3) to study the temporal dynamics of the distribution of aggregate size classes and of storage of OM within aggregates in the field. Surface soils (0-5 cm) and subsoils (10-20 cm) were sampled after fallow (March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 41 publications
2
20
1
Order By: Relevance
“…This may have been caused by the aging of the V. karroo leaves, which were harvested at the beginning of winter period (May). However, the results agreed with [13], who observed that C/N ratio had no influence on different forest litter material and suggested other factors such as lignin/N ratio or secondary metabolites like polyphenols to influence decomposability of litter.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This may have been caused by the aging of the V. karroo leaves, which were harvested at the beginning of winter period (May). However, the results agreed with [13], who observed that C/N ratio had no influence on different forest litter material and suggested other factors such as lignin/N ratio or secondary metabolites like polyphenols to influence decomposability of litter.…”
Section: Resultssupporting
confidence: 89%
“…Several studies have indicated that the chemical and biochemical quality of litter affects mass loss during decomposition [10,11]. The addition of higher quality substrate (lower C/N ratio of <24 and lower lignin content) resulted to increased SOC mineralization compared to the addition of lower quality (C/N ratio >24) substrate [12][13][14]. Since the soil microbes need N (and other essential elements) as well as C, if there is little N in the residue, decomposition is slow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Munoz-18 Rojas et al 2012;De Moraes Sá et al 2013;Gelaw et al 2013;Parras-Alcántara et al 2013, 201419 Srinivasarao et al 2014;Yu and Jia 2014;Behera et al 2015;Peng 2015). Agriculture can strongly 20 limit SOM accumulation, influencing soil aggregate formation and turnover (Jastrow 1996;Cerdà, 21 2000;Jacobs et al 2010;Gosling et al 2013). In particular, tillage can increase the turnover of 22 macroaggregates (Six et al 2000), consequently limiting the physical protection of SOM, hence the 23 formation of microaggregates inside macroaggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The stabilization of organic matter (OM) in soil (protection of OM against microbial decomposition) can mainly be attributed to three general mechanisms: spatial inaccessibility, biochemical recalcitrance and organo-mineral association [7]. The importance of these mechanisms can differ for each soil horizon and depends on several factors, such as soil type and texture, mineralogical composition and land use [11].…”
Section: Introductionmentioning
confidence: 99%